Look at Myself - Latimer, Lucas James (My University, 2023)
I have questions that need answers and I had questions yet to ask. That stumped me for a while. What would I look for as an artist and what would I do with the answers discovered? In this thesis, I will address why these questions are important to my art.”Rudimentary questions like “What are the reasons for making art or does what I produce make me an artist? and their answers would be presumably intuitive for artists, or at least that was how I felt before this master’s program. This could be summed up best by a Thomas Merton's quote, “Art enables us to find ourselves and lose ourselves at the same time.”
Thesis (Master's)--University of Washington, 2023
Keywords: Fine arts